4x+10+3=40x-3x

Simple and best practice solution for 4x+10+3=40x-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+10+3=40x-3x equation:


Simplifying
4x + 10 + 3 = 40x + -3x

Reorder the terms:
10 + 3 + 4x = 40x + -3x

Combine like terms: 10 + 3 = 13
13 + 4x = 40x + -3x

Combine like terms: 40x + -3x = 37x
13 + 4x = 37x

Solving
13 + 4x = 37x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-37x' to each side of the equation.
13 + 4x + -37x = 37x + -37x

Combine like terms: 4x + -37x = -33x
13 + -33x = 37x + -37x

Combine like terms: 37x + -37x = 0
13 + -33x = 0

Add '-13' to each side of the equation.
13 + -13 + -33x = 0 + -13

Combine like terms: 13 + -13 = 0
0 + -33x = 0 + -13
-33x = 0 + -13

Combine like terms: 0 + -13 = -13
-33x = -13

Divide each side by '-33'.
x = 0.3939393939

Simplifying
x = 0.3939393939

See similar equations:

| 4+5ln(x)=5 | | 4+ln(5)=5 | | 1.5t^4-3t^2+5t-1=0 | | 44x+3=45x | | x=1.5t^4-3t^2+5t-1 | | 45x+3=45x | | 4/3x-4=-3/4x-4 | | 51z-21=z-58 | | 11x+17=13x-1 | | n-51=24 | | 44x+2=44x+2 | | 5x-29y=-23 | | .7(x+5)+.4(x+25)=30 | | -3(-6n+3)-7n=-86 | | .1428(x+7)+.035(x-28)=x+23 | | x^2+2=102 | | 5b-5-12b-8= | | d(x)=2x-4 | | X=180+0.6(60+0.2x) | | Log(16+2x)=log(x^2-4x) | | X=180+0.6+(60+0.2) | | x^2-39x+376=0 | | X=180+0.6y | | 5x+1=-25-2x | | 80x^4+72x^3-47x^2-15x=0 | | 3t-15=2+10 | | (2+z)(4z-1)=0 | | 3cosx*sinx=1 | | 4x-18=3x+5 | | 6(t-2)+4t=5(2t+4)-9 | | (s)(-3st)(-1/3) | | y+115+65= |

Equations solver categories